Pengaruh Tingkat Pendidikan Orang Tua dan Disiplin Belajar Terhadap Prestasi Belajar Siswa SD - Ahmad Rustam; Desi Ratnasari; Anidi; Aris Suziman (Arden Jaya Publisher, 2023)
The purpose of this study was to determine the effect of parents' educational level and learning discipline on student achievement. The approach in this research is a quantitative approach. The population of this study were all fourth grade students at SD Negeri Lalonggaluku, totaling 45 students. The sample for this study used a total population of 24 students in class IV-A and 21 students in class IV-B. The research data was collected through the questionnaire method. Data analysis in this study used the SPSS 25 for Windows program. The results of the regression analysis obtained R Square 0.516, this means that the variable level of parental education (X1) and student learning discipline (X2) has an influence of 51.6% on student achievement (Y). Variable X1 gave an effective contribution (SE) of 2.77% and variable X2 of 48.83%, so it was concluded that the educational level of parents and student learning discipline had a positive effect on increasing student achievement in class IV SD Negeri Lalonggaluku.